2016
DOI: 10.1016/j.gdata.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic data of fungal internal transcribed spacer from serofluid dish, a traditional Chinese fermented food

Abstract: Serofluid dish (or Jiangshui, in Chinese), a traditional food in the Chinese culture for thousands of years, is made from vegetables by fermentation. In this work, microorganism community of the fermented serofluid dish was investigated by the culture-independent method. The metagenomic data in this article contains the sequences of fungal internal transcribed spacer (ITS) regions of rRNA genes from 12 different serofluid dish samples. The metagenome comprised of 50,865 average raw reads with an average of 8,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This is the first study to explore the fungal diversity of suansun with HTS. Ascomycota and Basidiomycota, the major phyla reported in many other kinds of fermented vegetables, 15,31 were also found to be predominant in this study. Unlike the differences in the bacterial communities between the two groups, the microbiota of fungi at the genus and species level in the two groups exhibited significant differences in this study.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is the first study to explore the fungal diversity of suansun with HTS. Ascomycota and Basidiomycota, the major phyla reported in many other kinds of fermented vegetables, 15,31 were also found to be predominant in this study. Unlike the differences in the bacterial communities between the two groups, the microbiota of fungi at the genus and species level in the two groups exhibited significant differences in this study.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Pichia and Debaryomyces, which have been reported to contribute to the volatile components of many fermented foods, such as wines, 33 Chinese liquors, 8 cheese 34 and soybean pastes, 35 are very common fermentation-associated yeast, and they were also detected in some other fermented vegetables, such as yancai, 25 zhacai, 15 and traditional Chinese fermented peppers. 31 Aspergillus and Candida are considered to be the core fungi for flavor formation in Kazak artisanal cheese. 36 Previous studies have reported that the microbial community structures that develop during the fermentation of vegetables are affected by many factors, such as the manufacturing process, the fermentation environment, and the geographical area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These microorganisms are especially relevant in directly brined olives due to the inhibition of LAB by the presence of phenolic compounds [ 5 6 , 9 ]. The only study on this matter was recently carried out by HiSeq Illumina sequencing to determine the fungal communities in serofluid dish, a traditional food in the Chinese culture made from vegetables by fermentation [ 37 ]. Candida and Sporpachydermia were the dominant genera found in that product.…”
Section: Discussionmentioning
confidence: 99%
“…Serofluid dish, a traditional Chinese salt-free food with a history of 2000 years, is an artisanal food fermented from vegetables such as celery and cabbage. 1,2 Serofluid dish is most prevalent in northwest China as a daily meal, with varying cooking and eating methods among different areas. It is also called Jiangshui in Chinese because of its white serofluid.…”
Section: Introductionmentioning
confidence: 99%